The effects of strain rate on nonlinear seismic behavior of concrete gravity dam - sara saemi ghassabmale; Amir Javad Moradloo (مهندسی و مدیریت ساخت, 2024)
Due to the large scale of concrete dams, it is difficult to conduct experimental studies on them and therefore, the numerical simulation is used in the dynamic analysis of such dams more effectively .In this study, the effects of strain rate on nonlinear seismic behavior of concrete gravity dam are presented using the plastic damage model. The compressive strength, tensile strength and fracture energy are important parameters for identifying and describing the concrete behavior. In dynamic loading, these parameters are affected by the strain rate. The plastic damage model use isotropic tensile failure as well as anisotropic compression plasticity to express non-linear behavior of concrete and can be sensitive to strain rate. The complete fluid-structure interaction was considered in the analyses. The damage patterns, displacement and stress distribution, and their time histories are investigated by considering the effects of strain rate on the nonlinear seismic behavior of dam. The deduce results indicates that pattern of cracking and distribution of displacement, stress and strain will changed considering strain rate.